EFEK PENGHAMBATAN KENAIKAN SGPT TABLET EKSTRAK CURCUMA TERHADAP KELINCI (Oryctolagus cuniculus) YANG DIBERI KLOROKUIN DAN TETRASIKLIN - Rahmawati, Rahmawati; Arisanti, Arisanti (Jurnal Ilmiah As-Syifaa, 2009)
This research’s aim to determined inhibition effect of the elevate of SGPT levels by Extract Curcuma Tablets had given Tetracycline and Chloroquine. This research use 12 male rabbits were classified into 4 groups. The first group is chloroquine, the second group is Tetracycline, the third group are chloroquine and Tetracycline, and the fourth are chloroquine –Tetracycline plus Curcuma Extract Tablets. Each of them was measured by SGPT measurement for 3 times. Before the treatment, the first week and the second week after the treatment. Statistical analysis was involved by One-way ANOVA Descriptives Analyzing Data. The result indicated that Curcuma Extract Tablets gift with hepatotoxic medicines could inhibited the elevate of SGPT levels.Key words : Hepatoprotector, chloroquine, SGPT, Tetracycline